SOLUTION:
Step 1:
In this question, we are meant to find the x-intercept and y-intercept of the graph of :
![\text{2x + 6y = 6}](https://img.qammunity.org/2023/formulas/mathematics/college/w7karbgr0l7idoxzbuxmtyhrhz3um38phr.png)
First, we are meant to graph it
Second, we are meant to find:
a) x-intercept
b) y - intercept
Step 2:
The graph of :
![\text{2 x + 6y = 6}](https://img.qammunity.org/2023/formulas/mathematics/college/xk0kjzuignrhbj4fhq39fmspzp8kivbq31.png)
is as follows:
Step 3:
Given the equation:
![\begin{gathered} 2x\text{ + 6y = 6} \\ For\text{ the x-intercept, we have that:} \\ \text{when y = 0, we have that:} \\ 2x\text{ + 6 (0 ) = 6} \\ 2\text{ x+ 0 = 6} \\ 2x\text{ = 6} \\ \text{Divide both sides by 2 , we have that:} \\ \text{x = }(6)/(2) \\ \text{x = 3} \\ \text{Then , the x - intercept = ( 3, 0 )} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bnb8qhr0i5vx1sluf9jtfx4gp4xaryyvaw.png)
Next, given the equation:
![\begin{gathered} 2x\text{ + 6 y = 6} \\ For\text{ the y - intercept, we have that:} \\ \text{when x = 0 , we have that:} \\ 2\text{ ( 0 ) + 6 y = 6} \\ 0\text{ + 6y = 6} \\ 6y\text{ = 6} \\ \text{Divide both sides by 6, we have that:} \\ y\text{ = }(6)/(6) \\ y\text{ = 1} \\ \text{Then , the y -intercept = ( 0 , 1 )} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bn1c5rgedebop0l49h06kb5xrxjiw6to81.png)